Assessment of facilities and reasons for settlement in old age homes of Himachal Pradesh, India - Kumar, Sanjay; Gupta, Anmol; Mazta, Salig Ram; Sharma, Deepak; Chaudhary, Ankit; Chamotra, Shaina (International Journal Of Community Medicine And Public Health, 2020)
Background: Ageing though a physiological phenomenon has massive implications on health status of an individual. Once a nation of joint families, India has also seen increase in nuclearization of families. This in-turn has led to increase in old age homes (OAHs) in our country and also increased number of admissions in such institutions. The present study evaluated such facilities in state of Himachal Pradesh and the reasons for the settlement among the occupants. Methods: A descriptive cross sectional study was conducted to capture socio-demographic variables, reasons for settlement, facilities available in such institutions, medical facilities provided and overall satisfaction level among the occupants of all seven OAHs of the state. After taking ethical considerations into account, data was collected and analyzed using appropriate statistical techniques. Results: A total of 145 inmates were included in the study. About 86.2% inmates belonged to rural area and about three fourth of the elderly were illiterate. About 53.8% of the inmates had no children with about 45.5% of participants having lost their spouse. About 19.3% individuals had no source of income. Most common cause for settlement in OAHs was the non-availability of a care giver. About 85% of inmates had satisfaction level of average and above. Conclusions: Considering the increase in elderly population in the country there is a need for increase in number of facilities for elderly too. Moreover there is a need for standardizing such institutions in term of infrastructure, staff and facilities, with more emphasis on medical aspect.